Evaluasi Strategi Pengembangan Usaha Petik Apel pada Kelompok Tani Makmur Abadi, Tulungrejo, Kota Batu - Mufida, Anis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Batu is a city that has big potention in tourism industry, this city is also famous as a city of producing apples, so we can say that apple has become an icon of Batu which is very well known by the public. Nature concept of tourism industry for example apples picking tourism concept in Batu is currently become a different and interesting thing for many tourists visiting Batu. Makmur Abadi farmer group is one of a farmers group in Batu that has apples picking business units. But over the time, with the improvement of tourism industry in Batu, the changes of the internal and external environment, exclude the situation of the competition in this industry, impact in there are many competitors who set up a similar business. The purpose of this paper is to explain the evaluation of apples picking business development strategies, include a description of the environmental changes that affect the performance of apples picking business units in Makmur Abadi farmers group, corrective steps that can be taken, the formulation of long-term goals, and short-term goals, as well as a new strategic plan for the apples picking business unit in the face of current environment developments, both internal and external environment . Keywords: farmers, tourism, apples picking, Batu City